2016
DOI: 10.1007/s00395-016-0559-0
|View full text |Cite
|
Sign up to set email alerts
|

Exercise does not activate the β3 adrenergic receptor–eNOS pathway, but reduces inducible NOS expression to protect the heart of obese diabetic mice

Abstract: Obesity and diabetes are associated with higher cardiac vulnerability to ischemia-reperfusion (IR). The cardioprotective effect of regular exercise has been attributed to β3-adrenergic receptor (β3AR) stimulation and increased endothelial nitric oxide synthase (eNOS) activation. Here, we evaluated the role of the β3AR-eNOS pathway and NOS isoforms in exercise-induced cardioprotection of C57Bl6 mice fed with high fat and sucrose diet (HFS) for 12 weeks and subjected or not to exercise training during the last 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 49 publications
1
40
0
Order By: Relevance
“…It was recently reported that exercise is able to enhance cardiomyocyte renewal [34, 42], which is necessary to mediate the protective effect of exercise against I/R injury [5]. Moreover, exercise is efficient to reduce cardiac I/R injury both at baseline and in obese diabetic condition, though different molecular mechanisms might be involved [9, 29]. It was previously reported that acute exercise (cycling) could trigger rapid release of EVs into the circulation that might be responsible for mediating its systemic beneficial effects also including the heart [18].…”
Section: Discussionmentioning
confidence: 99%
“…It was recently reported that exercise is able to enhance cardiomyocyte renewal [34, 42], which is necessary to mediate the protective effect of exercise against I/R injury [5]. Moreover, exercise is efficient to reduce cardiac I/R injury both at baseline and in obese diabetic condition, though different molecular mechanisms might be involved [9, 29]. It was previously reported that acute exercise (cycling) could trigger rapid release of EVs into the circulation that might be responsible for mediating its systemic beneficial effects also including the heart [18].…”
Section: Discussionmentioning
confidence: 99%
“…This susceptibility to ischemia-reperfusion injury has been reproduced in animal models [59, 60]. It remains unclear if mitochondrial dysfunction is the cause or the consequence of metabolic impairment, but it has clearly been associated with metabolic dysfunction in various metabolic tissues including pancreas, liver, skeletal muscle or adipose tissue [61, 62].…”
Section: Factors Affecting Mitochondrial Quality Controlmentioning
confidence: 99%
“…[34]. In a recent study, exercise training stimulated eNOS and reduced iNOS in control rats and normalized iNOS and showed no effect on eNOS in high fat fructose diet rats after ischemia reperfusion injury [36]. In the current experiment, exercise training demonstrated a significant reduction in the expression of NOS-2 in the cross-section of the left ventricles of the exercise-trained rats.…”
Section: Discussionmentioning
confidence: 60%